MaGoGreen: Teknologi Bio-Konversi Sampah Organik Sebagai Pakan Ternak Alternatif Memanfaatkan Larva Black Soldier Fly - Dewi Yuli Yana; Muslimin Muslimin; Karyati Karyati; Sri Sarminah; Emi Purwanti; karmini karmini; nanda khairil hakim (Fakultas Kehutanan dan Lingkungan Tropis, Universitas Mulawarman, 2022)
Waste utilization and management in a number of areas in Indonesia is still a complicated problem. One of the wise waste management efforts is by utilizing bioconversion technology with Black Soldier Fly maggot media that known as MaGoGreen (Maggot Go Green). The purpose of this community service is to provide counseling to the community about the use of organic waste through environmentally friendly waste management with bioconversion technology by utilizing Black Soldier Fly Larvae. This activity is expected to be an effort to educate breeders to get cheap, safe, and quality feed independently. This counseling was carried out in collaboration with the Trigona Kelulut Makmur Bee Cultivation Group (KBLTKM) in Bangun Rejo Village, Tenggarong Seberang District, Kutai Kartanegara Regency, East Kalimantan Province. The community service methods used include material presentation, practice of maggot cultivation from the preparation stage, egg hatching and maggot enlargement to breeding, distribution of brochures (leaflets), and ends with discussions and questions-answers. Extension participants received knowledge about bio-conversion technology of organic waste as an alternative animal feed ingredient by utilizing Black Soldier Fly Larvae. Most of the participants also felt compelled to carry out independent processing of organic waste into livestock food products.